Struktur Komunitas Karang Lunak Pada Kedalaman Berbeda di Teluk Jemeluk Amed, Kabupaten Karangasem, Bali - Putu Adi Prawira; Dwi Budi Wiyanto; I Gusti Ngurah Putra Dirgayusa (Fakultas Kelautan dan Perikanan Universitas Udayana, 2022)
Reef is ecosystem in tropical waters which rich of biota constituent, with high species diversity. One of biota that compiler coral reefs are soft corals (Octocorallia, Alcyionacea). The aim of this research is to know the soft coral community structure at different depths and the influence of the limiting factors of soft corals. Soft coral data retrieval is done in 3 observation points. Each depth research carried out by installing 6 transects quadrants through 100 meter transect line parallel to the shoreline. Data retrieval of water quality carried out on site research and laboratory testing. The water quality data taken include; temperature, brightness, salinity, pH, flow velocity, DO, depth, nitrate and phosphate. Retrieving data using the soft coral community structure. The highest density values found in every station a depth of 5 meters and the lowest at each station a depth of 15 meters. According to Odum (1971), the value of diversity in the research area included in the high category of H' ? 3.0, as well as to the value of uniformity in the high category at stations 1 and 3 on each depth of H ? 0.6 and at station 2 for each depth in the low category of E ? 0.4. According to Odum (1971), the value of dominance classified in the high category of 0.75 to 1.00, which means that there are species that dominate that Sinularia flexibillis except at a depth of 15 meters which is rated as moderate dominance. The observation of the condition of the community structure is still relatively good, as the limiting factor in the study area is very suitable for soft corals.